Business Development Strategy For Farmer Grousps Clove Oil (Syzygium aromaticum) as aroma therapy case Study: Forest Farmers Group (KTH) Buku Manyeku in Dorari Isa Village, Hiri Island District, Ternate City, North Maluku Province - Usman, Irene; HS, Nur Azizah; Radjaloa, Vhyda Hamidah Aulia (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research was conducted to the forest farmer group (KTH) Buku Manyeku in Dorari Isa Village, Hiri Island District, Ternate City. The research was conducted for approximately 2 months, from August to September 2024. This research uses mixed methods research that combines the combined methods of qualitative and quantitative approaches. The types of data used in this study are primary data and secondary data. Data collection techniques include 3 stages, namely observation, interviews, and documentation. The data analysis method uses income analysis and SWOT analysis. The results showed that the business income of the clove oil farmer group amounted to Rp. 6,698,382. Based on the results of the External Factor Analysis Summary (EFAS) analysis, it can be seen that the value of the opportunity factor (Opportunities) has a value of 2.28 and the value of the threat factor has a value of 1.01. This value can be interpreted that the clove oil business has a higher opportunity of 2.28 compared to the threat of 1.01 and obtained the value of the vertical axis, namely the value of the opportunity factor at a weight multiplied by rantig of 0.63. SWOT matrix diagram, there are several alternative strategies that can be made as a business development program including in using strengths and taking advantage of opportunities farmer groups can maximize the use of available clove raw materials by increasing processing efficiency to produce quality clove oil and utilizing effective promotional strategies to maximize market reach and increase consumer attractiveness to products.